Design of a modular solution for an autonomous vehicle for cargo transport and handling - Oliveira, H.D.B.C.L. de (2020)
Due to the globalization of markets, the industrial competitiveness has increased significantly in the recent years. Within this scope, the transportation of products inside industrial parks acquires special relevancy. One of the solutions is the use of autonomous guided vehicles. This work presents the design of a modular autonomous vehicle, capable of carrying heavy loads, which will improve the performance of industrial parks. This is a compact vehicle with low associated costs and good transport speeds. A drive system was designed, which will be capable of transporting the proposed loads. This design was carried out using simulations of the transport with loads, either in plane ground or in an industrial park. A structural analysis to the vehicle was also undertaken by the Finite Element Method, showing the points of the structure that require reinforcement for the different load cases. Finally, the required corrections were implemented, giving to the structure the ability to carry the desired loads. The end result was an autonomous vehicle with capacity to safely transport the imposed loads in the most efficient possible manner.